Protecting non-muslim: its implementation during early Muslim rule of Islamic Jerusalem - Nor, Mohd Roslan Mohd (Brill Academic Publishers, 2011)
Islamicjerusalem is a region of a great significant and has been given blessing (barakah) to all nations (li al-‘ālamīn). This barakah is not only for Muslims exclusively, but it is for all nations in this world, including to those Christians and Jews for their attention to the region. This is not only stated in the Quran, but most importantly it has been shown to the world during the Muslims rule over the region. This means that Muslims respect others and appreciate co-existence. It is interesting to note that the Quranic frameworks on eliminating racism, promoting equality and assurance of freedom and rights is being implemented since early days of Islam as can be noted in the case of Islamicjerusalem. When ‘Umar came to Islamicjerusalem, he has granted rights to the people, regardless of their races, beliefs and ideological differences. What was more important is to bring peace together within the society. Only then the people were able to live together and prosperity of civilization is guaranteed. This paper attempts to explore Quranic framework in dealing with this matter and link its implementation in Islamicjerusalem region during the early period of Islam.